Answer:
pretty sure the answer is 432 cm2 not sure im in a rush
Step-by-step explanation:
Step-by-step explanation:
Given that,
a)
X ~ Bernoulli
and Y ~ Bernoulli ![(y_x)](https://tex.z-dn.net/?f=%28y_x%29)
X + Y = Z
The possible value for Z are Z = 0 when X = 0 and Y = 0
and Z = 1 when X = 0 and Y = 1 or when X = 1 and Y = 0
If X and Y can not be both equal to 1 , then the probability mass function of the random variable Z takes on the value of 0 for any value of Z other than 0 and 1,
Therefore Z is a Bernoulli random variable
b)
If X and Y can not be both equal to 1
then,
or ![Y=1)\\](https://tex.z-dn.net/?f=Y%3D1%29%5C%5C)
and ![Y =1)](https://tex.z-dn.net/?f=Y%20%3D1%29)
![p_z = P(x=1)+P(Y=1)\\\\p_z=p_x+p_y](https://tex.z-dn.net/?f=p_z%20%3D%20P%28x%3D1%29%2BP%28Y%3D1%29%5C%5C%5C%5Cp_z%3Dp_x%2Bp_y)
c)
If both X = 1 and Y = 1 then Z = 2
The possible values of the random variable Z are 0, 1 and 2.
since a Bernoulli variable should be take on only values 0 and 1 the random variable Z does not have Bernoulli distribution
Answer:
x^2 - 10x + 25 = 17
Step-by-step explanation:
Please use " ^ " to denote exponentation:
x^2 - 10x = -8
x^2 - 10x + 25 = 17
x^2 - 10x + 25 = -8
x^2 - 10x - 25 = -33
Begin with x^2 - 10x = -8. Here's the process for completing the square:
1. Take half of the coefficient of x and square the result:
(1/2)(-10) = -5, and then (-5)^2 = + 25
2. Add this 25 to the first two terms of x^2 - 10x = -8 and also to the constant -8: x^2 - 10x + 25 = -8 + 25, or x^2 - 10x + 25 = 17
3. Match this result to one of the given possible answers. Turns out that the given possible answer matching our result is the first one:
x^2 - 10x + 25 = 17
Answer:
f(7) = -113
Step-by-step explanation:
Hello!
Substitute 7 for x in the equation.
<h3>Evaluate</h3>
- f(x) = -4x² + 10x + 13
- f(7) = -4(7)² + 10(7) + 13
- f(7) = -4(49) + 70 + 13
- f(7) = -196 + 70 + 13
- f(7) = -113
f(7) is -113.
I think the answer is 10, 20, and 4